Electric field induced second harmonic (EFISH) measurements of highly boron doped p-type Si/SiO2 - Neethling, Pieter Herman (Stellenbosch : Stellenbosch University, 2008)
Thesis (PhD (Physics))--Stellenbosch University, 2008.